Is the Generosity of Medicaid Home and Community‐Based Services Associated with Community Discharge from Skilled Nursing Facilities?. (20th August 2020) - Wang, S.; Temkin‐Greener, H.; Simning, A.; Tamara Konetzka, R.; Cai, Shubing
Abstract : Research Objective: While most older adults receiving post‐acute care in skilled nursing facilities (SNFs) prefer to return home, many remain as nursing home (NH) long‐stayers due to lack of sufficient supports in the community. Discharge from SNF to the community may be particular challenging for Medicare‐Medicaid dually enrolled SNF users. Medicaid home and community‐based services (HCBS) have been expanding in the last few decades and could be an important source of community support for duals. The objective of this study was to examine whether the generosity of Medicaid HCBS is related to community discharge for dual SNF users. Study Design: National Medicare enrollment and claims data, Medicaid Analytic eXtract (MAX), Minimum Data Set, and facility/county‐level public available data between 2010 and 2013 were linked. Eligible Medicare‐Medicaid dual beneficiaries and their SNF post‐acute admissions were identified. Generosity of Medicaid HCBS was measured at the county level based on MAX data and included metrics for breadth (ie, proportion of duals using HCBS services) and intensity (ie, average HCBS spending per user). Outcome was community discharge within 100 days of SNF admission (dichotomous). A linear probability model with SNF fixed‐effects and robust standard errors was estimated to examine the relationship between the likelihood of community discharge and HCBS generosity, accounting for individual‐level covariates (eg, sociodemographic characteristic, characteristics of index hospital stay, history of hospitalization, functioning status, and comorbidities). We further stratified the analysis by age, type of index hospitalization, and presence of Medicaid lesser‐of policy, a cost‐sharing policy that limits the reimbursement received by SNFs for taking care of duals. Population Studied: Community‐dwelling older duals with fee‐for‐service (FFS) Medicare and Medicaid benefits who were newly admitted to SNFs for post‐acute care between October 1, 2010, and September 30, 2013 (N = 224 236). Principal Findings: HCBS breadth and intensity varied substantially across counties and over time. Overall, 49.4% of the identified dual SNF residents were discharged to community within 100 days of SNF admission. After accounting for covariates and SNF fixed‐effects, we found that a 10 percentage‐point increase in HCBS breadth led to a 0.66 percentage‐point increase ( P < 0.01) in the likelihood of discharge among older dual SNF users, but we did not detect a significant relationship between HCBS intensity and community discharge. Stratified analyses suggested a positive relationship between community discharge and HCBS breadth only among duals over 85 years old (1.49 percentage‐point, P < 0.01), and among those who had medical (vs surgical) index hospitalization (0.70 percentage‐point, P < 0.05). A stronger effect was found for states without Medicaid lesser‐of policy (2.26 percentage‐point, P < 0.05), compared to states with such a policy (0.53 percentage‐point, P < 0.05). Conclusions: We found that higher HCBS breadth but not intensity was related to a higher likelihood of community discharge with a relatively small effect size. The potentially meaningful effect was found among subgroups including the oldest old, people had medical index hospitalization, and states without Medicaid lesser‐off policy. Implications for Policy or Practice: While the effect of HCBS breadth on facilitating community discharge is modest in general, tailored HCBS policies to increase the coverage for targeted populations or in certain regions may be more effective in promoting community discharge. Primary Funding Source: National Institutes of Health.